Understanding the use of chemical and natural coagulants in the coagulation process: a review - Mohd Zin, Nur Shaylinda; Abdul Aziz, Hamidi; Mohd Adlan, Nordin; Ariffin, Azlan; Yusoff, Mohd Suffian (2012)
This paper reviews the application of natural and chemical coagulants for the treatment of various types of untreated water. Coagulation is a relatively simple pollutant removal process that has been used in most water and wastewater treatment systems. It involves the addition of a coagulant (chemical or organic) to untreated water to destabilize suspended matter, colloids, and others substances, causing them to be transformed into a larger size so they can be easily removed later on. The whole process reduces turbidity and the presence of dissolved chemical species in untreated water. The effectiveness of coagulation is related to the nature of the liquid to be treated. Different types of liquids such as water, wastewater, and leachate can influence the performance rate of coagulation. Treatability also depends on the type of coagulant used. In the past, conventional coagulants such as alum had shown a higher treatability rate for various liquids, but because of the high residual of aluminum, this coagulant had been found harmful to humans and the environment. The search for an alternative has resulted in the development of pre-polymerized, composite, and natural coagulants that can reduce the negative effects of conventional ones. At present, however, alternative coagulants are rarely used for several reasons.